2022
DOI: 10.3390/healthcare10071271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sub-Clinical and Clinical Compression Socks on Postural Stability Tasks among Individuals with Ankle Instability

Abstract: Compression socks are used by a very diverse group of individuals and may potentially have a greater impact on physically diminished or impaired individuals as opposed to healthy individuals. The purpose of this study was to compare the effects of sub-clinical (SC) and clinical (CL) compression socks among healthy (CON), copers (COP), and individuals with chronic ankle instability (CAI). Postural stability was evaluated in 20 participants (11 males and 9 females) using Balance Tracking System Balance platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Transmission intensity is associated with the average age at which children experience serious incidents of malaria. Children suffer more from symptomatic malaria at a younger age in areas of high transmission [19]. Usually, the risk of malaria incidence is positively related to the age, meaning people have more chance of getting malaria incidence the older they are [41].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Transmission intensity is associated with the average age at which children experience serious incidents of malaria. Children suffer more from symptomatic malaria at a younger age in areas of high transmission [19]. Usually, the risk of malaria incidence is positively related to the age, meaning people have more chance of getting malaria incidence the older they are [41].…”
Section: Agementioning
confidence: 99%
“…WHO is continuously putting its effort to control and eradicate malaria through the global malaria program that sets an aim to eradicate malaria from the world by 2030 with its long-term visionary initiative "Global technical strategy for malaria 2016-2030" [9]. Additionally, there are several organizations that have been funding to prevent and control malaria worldwide, such as the US Agency for International Development, World Bank, and Bill and Melinda Gates Foundation [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These mechanical properties of hydrogel electrolytes are of great importance, as they determine how well flexible and wearable supercapacitors can fit the wearer and how comfortable they are to wear. [243][244][245] This part of review covers recent advances in MXenenanocellulose composites for energy storage and generation applications. The composites are made into lithium-sulfur battery cathodes and supercapacitor electrodes, leveraging MXene's conductivity and high surface area.…”
Section: Power Generation and Energy Storagementioning
confidence: 99%
“…These mechanical properties of hydrogel electrolytes are of great importance, as they determine how well flexible and wearable supercapacitors can fit the wearer and how comfortable they are to wear. [ 243–245 ]…”
Section: Applications Of Mxene Nanocellulose‐based Hydrogel and Aerogelsmentioning
confidence: 99%
“…The general and specialized processes involved in controlling the stance and swing phases of gait are influenced by sensory feedback from specific skin regions on the foot [ 17 ]. Another study found that using compression stockings significantly reduced postural sway and improved balancing time [ 22 ].…”
Section: Introductionmentioning
confidence: 99%